Embedded smart GFRP reinforcements for monitoring reinforced concrete flexural components - Georgiades, Tasos; Saha, Gobinda C.; Kalamkarov, Alexander L.; Rokkam, Srujan K.; Newhook, John P.; Challagulla, Krishna S. (My University, 2005)
The main objectives of this paper are to demonstrate the feasibility of using newly developed smart GFRP reinforcements to effectively monitor reinforced concrete beams subjected to flexural and creep loads, and to develop non-linear numerical models to predict the behavior of these beams. The smart glass fiber-reinforced polymer (GFRP) rebars are fabricated using a modified pultrusion process, which allows the simultaneous embeddement of Fabry-Perot fiber-optic sensors within them. Two beams are subjected to static and repeated loads (until failure), and a third one is under long-term investigation for assessment of its creep behavior. The accuracy and reliability of the strain readings from the embedded sensors are verified by comparison with corresponding readings from surface attached electrical strain gages. Nonlinear finite element modeling of the smart concrete beams is subsequently performed. These models are shown to be effective in predicting various parameters of interest such as crack patterns, failure loads, strains and stresses. The strain values computed by these numerical models agree well with corresponding readings from the embedded fiber-optic sensors.
Keywords: smart GFRP rebar; Fabry-Perot sensors; structural strain and deformation; creep; finite element modeling